2017–2018 Assisted Reproduction Cost Analysis Performance Indexes: Lombardy County Case Study - Levi-Setti, Paolo Emanuele; Busnelli, Andrea; Bodina, Annalisa; De Luca, Roberto; Scaravelli, Giulia (Frontiers in Reproductive Health, 2021)
Objective: The aim of the present study was to analyze the IVF success rates and the economic cost per delivery in all the public funded IVF Units in Lombardy in the 2017–2018 period and to assess any significant difference in ART outcomes among the enrolled centers. Methods: Analysis of costs for the 2017 and 2018 fresh transfer delivery rate (DR) and Cumulative delivery rate (CDR) considering both fresh and frozen cycles were extracted from the ART Italian Registry on oocytes retrievals, fresh and frozen embryos and oocytes embryo transfer performed in 22 Lombardy IVF Units. Results: In 2017, 29,718 procedures were performed, resulting in 4,543 pregnancies and 3,253 deliveries. In 2018, there were 29,708 procedures, 4,665 pregnancies and 3,348 deliveries. Pregnancies lost to follow up were 5.0% with a (range of 0–67.68%) in 2017 and 3.4% (range of 0–45.1%) in 2018. The cost reimbursement for the cycles were €2,232 (2,611) for oocyte retrieval and €2,194 (2,567) for embryo transfer, excluding ovarian stimulation therapy and luteal phase support. 19.33 (5.80). The DR was 13.23 ± 5.69% (range 2.86–29.11%) in 2017 and 19.33 ± 5.80% in 2018 (range 11.82–34.98 %) and the CDR was 19.86 ± 9.38% (range 4.43–37.88%) in 2017 and 21.32 ± 8.84% (range 4.24–37.11%). The mean multiple pregnancy delivery rate (MDR) was 11.08 ± 5.55% (range 0.00–22.73%) in 2017 and 10.41 ± 4.99% (range 1.33–22.22%) in 2018. The mean CDR cost in euros was 26,227 ± 14,737 in 2017 and 25,018 ± 16,039 in 2018. The mean CDR cost among centers was 12,480 to 76,725 in 2017 and 12,973 to 86,203 in 2018. Conclusions: Our findings show impressive differences in the DR and CDR among centers and the importance of cryopreservation in patients' safety and economic cost reduction suggesting the formulation of specific KPI's (Key performance indexes) and minimal performance indexes (PI) as a basis for the allocation of public or insurance resources. In particular, the reduction of multiple pregnancy rates costs, may lead to a more widespread use of ART even in lower resources countries.